Marrubium deserti de Noé: Potential Candidate to Treat Oxidative Stress and Inflammation - Iqbal, Muhammad Naeem; Irfan, Muhammad (PSM Biological Research, 2021)
Marrubium deserti is a small perennial shrub, branched, with woolly leaves and stems. Its flowers are pale violet or pink. The plant has been used in traditional medicine for centuries. The leaves, stems, and flowers are used against intestinal disorders, respiratory diseases, fever, cough, dysmenorrhea, scorpion stings, and allergies. Marrubium sp. is known to have a large number of phytochemicals which are a group of compounds, belonging to secondary metabolites of plants. Many of these plant metabolites have been tested on animal and human cells, showing very interesting biological activities. In this issue, Ghedadba et al. report the antioxidant and anti-inflammatory activity of methanolic (MeOH) extract of M. deserti leaves. It demonstrates the large interest in phytochemicals and the potential use of M. deserti in the management of various disorders like oxidative stress and inflammation.